Social security programs and retirement around the world : micro-estimation - Gruber, Jonathan; Wise, David A. (National Bureau of Economic Research conference report., 2004)
Social Security Programs and Retirement around the World represents the second stage of an ongoing research project studying the relationship between social security and labor. In the first volume, Jonathan Gruber and David A. Wise revealed enormous disincentives to continued work at older ages in developed countries. Provisions of many social security programs typically encourage retirement by reducing pay for work, inducing older employees to leave the labor force early and magnifying the financial burden caused by an aging population. At a certain age there is simply no financial benefit to.